Measuring the Service Quality Gape in Commercial Banks: A Case Study of a Sample of Commercial Banks Customers in Oum El Bouaghi - HASSANI , Abdelakrim; BOUKETIR, Djebar (Journal of Finance & Corporate Governance, 2019)
This study aimed to measure the gap between expectation service quality and perception service quality in the banks of Public sectors in Algeria. To attain the aim of this study a random sample of customers was chosen to conduct this study within. Data were collected from 251 customers of public banks sector using structured questionnaire, this questionnaire was designed and applied to measure expectations and perceptions of customers. For the purpose of this study, we use certain statistical analysis methods such as paired T-test, means, to test study’s hypothesis. The results of statistical analysis showed that there are significant statistical differences between the expectations and perceptions of the customers with respect to all service quality dimensions (tangibility, reliability, responsiveness, assurance, empathy). Also results shows that there is a negative gap between the expectations and perceptions of the customers with respect to all service quality dimensions.